The view from Vevey - Madsen, Stig Toft (2001)
Most writings on globalisation exemplify technological globalisation by referring to the importance of computer technology in international trade. In this paper, the focus is on the technology of genetic engineering. A recurring issues in the debate on globalisation is the question whether globalisation leads to homogenisation. This paper attempts a closer look at the nuances within the `social movements' protesting globalisation, especially the farmers' movements and the Indian farmers' Inter-Continental Caravan (ICC) and the processes accompanying the resistance to globalisation, including perceptions of new technologies such as biotechnology. - Reproduced
Keywords: Science and technology; Biotechnology